Auction Platform Design and the Linkage Principle1. (June 2016) - Tamura, Wataru
Abstract : This paper examines an auction platform in which the monopoly platform maximizes profits by adjusting participation fees and choosing an auction format. The seller has private information on the quality of the good, and each participating buyer receives a private signal about his valuation of the good. The choice of auction format determines the allocation of trading surplus between the seller and buyers. This paper shows that when the seller's type is affiliated with the buyers' signals, the platform can charge higher participation fees on both sides by choosing a first‐price or descending auction than a second‐price or ascending auction.